2013
DOI: 10.2146/ajhp120639
|View full text |Cite
|
Sign up to set email alerts
|

National survey of pharmacy residency on-call programs

Abstract: Among usable responses to a survey of pharmacy residency programs, 29% indicated that their program included an on-call component. On-call programs varied greatly in activities, location, hours, and requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A pharmacy on‐call program is any clinical and/or administrative pharmacy service provided by a pharmacy resident outside of their rotational responsibilities or clinical pharmacist role outside of usual business hours (eg, 8 am ‐5 pm ). This may include drug information support, emergency response activities, patient education, drug‐dosing recommendations, pharmacokinetic drug monitoring, and drug shortage issues . Incorporating pharmacy residents into on‐call programs in addition to their rotational responsibilities has been utilized as a part of residents' service commitment within pharmacy residency training for at least 40 years .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A pharmacy on‐call program is any clinical and/or administrative pharmacy service provided by a pharmacy resident outside of their rotational responsibilities or clinical pharmacist role outside of usual business hours (eg, 8 am ‐5 pm ). This may include drug information support, emergency response activities, patient education, drug‐dosing recommendations, pharmacokinetic drug monitoring, and drug shortage issues . Incorporating pharmacy residents into on‐call programs in addition to their rotational responsibilities has been utilized as a part of residents' service commitment within pharmacy residency training for at least 40 years .…”
Section: Introductionmentioning
confidence: 99%
“…This may include drug information support, emergency response activities, patient education, drug‐dosing recommendations, pharmacokinetic drug monitoring, and drug shortage issues . Incorporating pharmacy residents into on‐call programs in addition to their rotational responsibilities has been utilized as a part of residents' service commitment within pharmacy residency training for at least 40 years . A 2010 survey of postgraduate year one (PGY1) residency program directors within the University Health‐System Consortium found that 23.5% (16/68) of respondents reported their residents had on‐call responsibilities as a part of their residency staffing component .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several hospital pharmacy practice residencies have added an overnight or on-call component to their program. [1][2][3] As a result of all these factors, offering night-shift experiential rotations to pharmacy students provides exposure to a potential practice environment and refines problem-solving abilities. This commentary will detail an experience as a preceptor for a night-shift hospital Introductory Pharmacy Practice Experience (IPPE) and discuss the value of night-shift rotations.…”
Section: Introductionmentioning
confidence: 99%